Effectiveness of Household-Based Poverty Programs: Lesson Learn from Indonesia - Meydianawathi, Luh Gede; Setyari, Ni Putu Wiwin (Muhammadiyah University Press, 2018)
implemented in fact it does not negates the poor, but at least they try to reduce the amount. Indonesia so far has various poverty programs aimed at different groups based on the primary target, ranging from household (cluster one), a community or group of communities (clusters two), and small and medium enterprises (cluster three). This study aims to look at the effectiveness of the implementation of the government's poverty programs mainly intended for households. Specific target to be achieved is nothing but a refinement of the targeting mechanisms and beneficiaries of the program. The results are expected to contribute to the policy assessments of poverty alleviation program and their perfecting in the future. Analyzes used data of Indonesia Family Life Survey (IFLS) in 2007 and 2014. In accordance with its objectives, there are three policies that would be seen its impact on household welfare indicators, namely the health policy (ASKESKIN), consumption policy (BLT) and education policy (BSM). The test results show if the three policies programs targeting households poverty alleviation do not have the same effect on the changes in household income. Direct cash assistance (consumption policy/BLT) was most effective compared to other programs. Therefore it can be concluded if these three programs have different effects at different time periods, so it must be applied in accordance with the needs.